Expression 8: 3 "x" equals "y" plus 11 left brace, 2.3 less than or equal to "x" less than or equal to 2.6 , right brace3x=y+112.3≤x≤2.6
8
Expression 9: negative 2 "y" equals "x" plus 6 left brace, negative 4.1 2 less than or equal to "y" less than or equal to negative 3.7 , right brace−2y=x+6−4.12≤y≤−3.7
9
Expression 10: 6 left parenthesis, "x" minus 3 plus 4 , right parenthesis squared plus left parenthesis, "y" plus negative .1 plus negative .3 , right parenthesis squared equals .46x−3+42+y+−.1+−.32=.4
10
Expression 11: 6 left parenthesis, "x" minus 3 plus 2.5 , right parenthesis squared plus left parenthesis, "y" plus negative .2 plus negative .5 , right parenthesis squared equals .46x−3+2.52+y+−.2+−.52=.4
11
Expression 12: negative "x" equals negative left parenthesis, "y" minus negative 2 , right parenthesis squared plus 4 left brace, negative 4 less than or equal to "x" less than or equal to negative 2 , right brace−x=−y−−22+4−4≤x≤−2
12
Expression 13: negative "x" equals negative left parenthesis, "y" plus negative 3.2 , right parenthesis squared plus 1 left brace, negative 1 less than or equal to "x" less than or equal to negative .6 , right brace−x=−y+−3.22+1−1≤x≤−.6
13
Expression 14: "x" equals negative 2 left parenthesis, "y" minus negative 1.2 , right parenthesis squared plus 5 left brace, 3 less than or equal to "x" less than or equal to 5 , right bracex=−2y−−1.22+53≤x≤5
14
Expression 15: "x" equals negative 2 left parenthesis, "y" plus negative 2 , right parenthesis squared plus negative 2 left brace, 2 less than or equal to "y" less than or equal to 2.8 , right bracex=−2y+−22+−22≤y≤2.8